The Effect of 16 Weeks of Lower-Limb Strength Training in Jumping Performance of Ballet Dancers - Ávila-Carvalho, Lurdes; Conceição, Filipe; Escobar-Álvarez, Juan A.; Gondra, Beatriz; Leite, Isaura; Rama, Luís (Frontiers in Physiology, 2022)
Jumping ability is considered a determinant of performance success. It is identified as one of the predictors and talent identification in many sports and in dance. This study aimed to investigate the effect of 16 weeks of lower limb strength training in the jumping performance of Ballet dancers. 24 participants from the same dance school were randomly allocated into control (CG; n=10; 13.00 (1.49) years old; 43.09 (9.48) kg and 1.53 (0.11) m) and intervention group (IG; n=14; 12.43 (1.45) years old; 38.21 (4.38) kg and 1.51 (0.07) m), evaluated pre and post the applied strength training program mainly using one’s body weight. Jump performance was assessed through the MyJump2, a scientific validated mobile phone app. Intergroup and intragroup comparisons were assessed, and the magnitude of change was calculated using the effect size (ES). While CG significantly decreased the Relative Power over time (p<0.001, ES=-0.29: small), results from the intragroup comparisons suggest that IG significantly increased the CMJ height (p<0.001, ES=1.21: large); the Relative Force (p<0.001, ES=0.86: moderate), Maximal Velocity (p<0.001, ES=1.15: moderate) and Relative Power (p<0.001, ES=1.37: large). We concluded that a 16-week strength training program of lower limbs is an effective way to improve CMJ height in young dancers. Supplementary strength training appears to be determinant for the improvement of the jumping performance of ballet dancers.